The Effect of Financial Literacy Level, Payment System, Local Culture, Brand Image, Marketing Strategy, and Customer Relationship Management on Consumer Purchasing Decisions - Peri Peri*; Yeni Pronika; Safira Wahyuni; Darman Saputra (Universitas Syiah Kuala, 2023)
TanahWari is a signature product of Bangka Belitung that combines fashion with historical values in every motif. The first motif they used was inspired by the Menumbing pesanggerahan building, a historical building in the determination of Indonesian independence located in Muntok City, West Bangka Regency. This study aims to see what factors influence consumer purchasing decisions for products in TanahWari. The type of research used in this research is quantitative research. The data used is primary data in the form of data collection such as information or information from interviews and questionnaires from buyers of TanahWari products and secondary data in the form of various relevant literature, books, journals and documentation. With this MSME, it is hoped that it can meet the needs of fashion and support the economy in Pangkalpinang City, Bangka Belitung. By pouring Bangka Belitung's distinctive motifs into marketed products, it is hoped that it can increase public awareness about the importance of preserving culture and local wisdom in Bangka Belitung.